(3HQgGf GdHQgGf GdQGFV aj GdLHQ hGdMSGH hGdNWCjf hGdCbOGQ hGdaQGFVs - (3UGQe GdOjf EHQGgje Hf YeQ Hf Ydj Hf CHj HcQ Hf eMeO, GdfLdj GdMfajs
(3ChdgG (B:s
(3GdMeOddg GdPi dG jYRH CeQ Yf EMGWJg hYdeg s
(3cGf ehLhOkG SfI (B909 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B94 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B20 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs